**Let the number in the tenth's digit be x and the number in one's digit be y. The number thus obtained = 10x + y**

**On reversing the digits we get : 10y + x**

**Now, according to the question, we have**

**(10x + y) - (10y + x) = 36**

**= 10x - x + y - 10y = 36**

**= 9x - 9y = 36**

**= x - y = 4**

**= x = 4 + y ............ (i)**

**Next we check the values of the options and check which statement is false.**

**a) We apply x + y = 6 (x + y is the sum of the digits)**

**Substituting value of x from (i), we get :**

**(4 + y) + y = 6**

**= 4 + 2y = 6**

**= 2y = 2**

**= y = 1 (The value of y can be 1 so the statement is true)**

**b) We apply x + y = 8**

**Substituting value of x from (i), we get :**

**(4 + y) + y = 8**

**= 4 + 2y = 8**

**= 2y = 4**

**= y = 2 (The value of y can be 2 so this statement is also true)**

**c) We apply the value x + y = 9**

**Substituting value of x from (i), we get :**

**(4 + y) + y = 9**

**= 4 + 2y = 9**

**= 2y = 5**

**= y = 5/2 (The value of y can never be a fraction so the statement is false)**

__Therefore the answer is option c) 9__

**Hope that helps !!**